EFFICIENT AND RELIABLE PUBLIC HEALTHCARE SERVICES WITH G-CLOUD INFRASTRUCTURE (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
An improvised social insurance system is required in light of the limitations of the outdated medical care framework and the progress of technology. In the human services industry, cloud-based software development is becoming more and more popular as a means of managing and fulfilling current and future demands in social insurance administrations. We suggest a flexible, secure, effective, useful, and protected cloud-based framework for medical services. We've provided a secure and efficient framework for the administration EHR, where access control arrangements are made possible by many tiers of information structure and multi-authority ciphertext property based encryption (CP-ABE), which governs fine-grained access control. Top Saudi officials stand to gain greatly from egovernment distributed computing, since the planned framework will enable them to expand their social insurance industry.